Homogenization results for a Landau–Lifshitz–Gilbert equation in composite materials with transmission defects. Issue 12 (13th August 2022) - Choquet, C.; Ouhadan, M.; Tilioua, M.
Abstract : We study the homogenization of Landau–Lifshitz–Gilbert equation in a ϵ -periodic composite material formed by two constituents, separated by an imperfect interface Γ ϵ, on which we prescribe the continuity of the conormal derivatives and a jump of the solution proportional to the conormal derivative, by means of a coefficient of order ϵ γ . We use the periodic unfolding method together with extension operators for handling the nonlinearities to identify the limit problem when tuning up the parameter γ in R .